2015
DOI: 10.1186/s12893-015-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

A case report of a solitary pancreatic metastasis of an adrenocortical carcinoma

Abstract: BackgroundSolitary metastases to the pancreas are rare. Therefore the value of resection in curative intention remains unclear. In the literature there are several promising reports about resection of solitary metastasis to the pancreas mainly of renal origin.Case presentationHere we report for the first time on the surgical therapy of a 1.5 cm solitary pancreatic metastasis of an adrenocortical carcinoma. The metastasis occurred almost 6 years after resection of the primary tumor. A partial pancreatoduodenect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The common sites of distant metastases of ACC are liver, lung, and bone [ 65 ]. Unusual descripted metastatic locations of ACC have been reported in the stomach [ 66 ], pancreas [ 67 ], skin [ 68 ], spleen [ 69 ], tongue [ 70 ] and brain including meninges [ 71 , 72 ]. Recurrence and distant metastases of ACC often occur quickly (within 2 years).…”
Section: Conventional Adrenocortical Carcinomamentioning
confidence: 99%
“…The common sites of distant metastases of ACC are liver, lung, and bone [ 65 ]. Unusual descripted metastatic locations of ACC have been reported in the stomach [ 66 ], pancreas [ 67 ], skin [ 68 ], spleen [ 69 ], tongue [ 70 ] and brain including meninges [ 71 , 72 ]. Recurrence and distant metastases of ACC often occur quickly (within 2 years).…”
Section: Conventional Adrenocortical Carcinomamentioning
confidence: 99%
“…Baur et al reported a case of pancreatic metastasis from ACC. Their case was one of recurrent ACC with a solitary pancreatic metastasis that occurred six years after resection of the primary tumor (7).…”
Section: Discussionmentioning
confidence: 99%